Penyuluhan dan Pelatihan Kesehatan Gigi dan Mulut pada Umat Lansia Gereja Santo Andreas - Talenta Theresia, Tiarma; Juliawati, Mita; Tanjung, Rizki; Dipankara, Jackson; Nursolihati, Vidya (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Oral health is essential in maintaining quality of life, especially in the elderly. The elderly tend to experience decreased oral function due to physiological changes and a lack of knowledge regarding proper care. This counseling and training activity aims to increase the understanding and skills of the elderly at Santo Andreas Church in caring for oral hygiene and health independently. This activity was conducted utilizing counseling and health services on June 21, 2025, for 37 elderly people in the Mutiara Senja Elderly Community of Santo Andreas Church, West Jakarta. The methods used include interactive delivery of educational material and hands-on training tailored to the target group's needs. Evaluation was carried out through a pre-test and a post-test to assess the increase in participants' knowledge. The activity results showed a significant increase in the understanding of the elderly about the importance of maintaining oral health from the pre-test and post-test results.